The Linkage Between Virtual Team Leadership Towards Team Performance: A Study at Selected Companies - Ab Wahab, NurulJannah; Abdullah, Nor Hazana; Rodzalan, Shazaitul Azreen; Rahman, Zainur (Journal of Techno-Social, 2023)
Since the outbreak of COVID-19, virtual teams have added significant presence in the workplace. Despite being unable to meet each other physically, virtual team members utilize various digital technologies to communicate with each another to carry out activities and achieve organizational goals. However, there are limited studies identifying the linkage between virtual team leadership and team performance despite its prominence. Therefore, this study aims to examine the link between virtual team leadership and team performance among work remote employees working in virtual environment. The survey was distributed to a sample size of 338 remote employees among selected companies that agreed to participate with a response rate of 27.6 percent (105 respondents). The collected data were analyzed using both descriptive and inferential statistics via IBM Statistical Package for the Social Sciences (SPSS). It is found that virtual team leadership have positive significant effect on team performance. In particular, virtual leaders who communicate well through virtual platform would affect the team performance. This indicates the need for existing leaders to be equipped with the latest know-how on digital communication.